Methods Used to Increase and Promote the Academic Interest of the Electromagnetic Compatibility Course Content in the Engineers’ Education - ACIU Lia Elena; GHIȚĂ-PÎRNUȚĂ Oana-Andreea; OGRUTAN Petre Lucian (TEM Journal, 2024)
Electromagnetic compatibility (EMC) is an academic subject which, due to its mathematical support, is considered to be difficult by the students.Multifarious methods have been applied in order to increase the academic interest of this subject. They include project based learning (PBL)–type activities for the laboratory sessions and within the framework of some elective activities. Students are interested in the current problems of society, so addressing some problems that concern the modern world, such as the effect of electromagnetic radiation on health, contributes to increasing the academic interest in the subject. The methods described in the present paper have led to an increase of the academic performance, which stands as proof for a smaller number of students who need to retake examinations, for higher scores and even the publication of scientific papers with the students’ input.